Litter decomposition rates across tropical montane and lowland forests are controlled foremost by climate. (17th December 2021) - Ostertag, Rebecca; Restrepo, Carla; Dalling, James W.; Martin, Patrick H.; Abiem, Iveren; Aiba, Shin‐ichiro; Alvarez‐Dávila, Esteban; Aragón, Roxana; Ataroff, Michelle; Chapman, Hazel; Cueva‐Agila, Augusta Y.; Fadrique, Belen; et al.
Abstract: The "hierarchy of factors" hypothesis states that decomposition rates are controlled primarily by climatic, followed by biological and soil variables. Tropical montane forests (TMF) are globally important ecosystems, yet there have been limited efforts to provide a biome‐scale characterization of litter decomposition. We designed a common litter decomposition experiment replicated in 23 tropical montane sites across the Americas, Asia, and Africa and combined these results with a previous study of 23 sites in tropical lowland forests (TLF). Specifically, we investigated (1) spatial heterogeneity in decomposition, (2) the relative importance of biological factors that affect leaf and wood decomposition in TMF, and (3) the role of climate in determining leaf litter decomposition rates within and across the TMF and TLF biomes. Litterbags of two mesh sizes containing Laurus nobilis leaves or birchwood popsicle sticks were spatially dispersed and incubated in TMF sites, for 3 and 7 months on the soil surface and at 10–15 cm depth. The within‐site replication demonstrated spatial variability in mass loss. Within TMF, litter type was the predominant biological factor influencing decomposition (leaves > wood), with mesh and burial effects playing a minor role. When comparing across TMF and TLF, climate was the predominant control over decomposition, but the Yasso07 global model (based on mean annual temperature and precipitation) only modestly predicted decomposition rate. Differences in controlling factors between biomes suggest that TMF, with their high rates of carbon storage, must be explicitly considered when developing theory and models to elucidate carbon cycling rates in the tropics. Abstract in Spanish is available with online material. Abstract : In a common litter decomposition experiment with contributors from 23 tropical montane forest (TMF) sites across the Americas, Asia, and Africa, we investigated controls of leaf and wood litter decomposition and compared to tropical lowland forests and combined these results with a previous study of 23 sites in tropical lowland forests (TLF). Climate was the predominant control over decomposition in both biomes, but played a greater relative role over biological factors in the TMF. The carbon stores of these iconic montane forests of the tropics face threats from climate change and deserve more attention in global ecosystem studies. Resumen: La hipótesis de la "jerarquía de factores" en la descomposición establece que las tasas globales de descomposición de hojarasca están controladas principalmente por el clima, seguido de variables biológicas y edáficas. Los bosques tropicales de montaña (BTM) son ecosistemas de importancia global, sin embargo, ha habido esfuerzos limitados para caracterizar las tasas de descomposición de hojarasca a la escala de este bioma. Diseñamos un experimento común para la descomposición de hojarasca replicado en 23 sitios tropicales de montaña distribuidos en los continentes de América, Asia y África, y combinamos los resultados con un estudio previo que incluyó 23 sitios en bosques tropicales bajos (BTB) para examinar la contribución de los BTMs solos y en combinación con las tasas de descomposición de BTB. Específicamente, investigamos (1) la heterogeneidad espacial de la descomposición; (2) la importancia relativa de factores biológicos que afectan la descomposición de hojas y madera en BTM; y (3) el rol del clima en determinar las tasas de descomposición de hojarasca en los biomas BTM y BTB. Incubamos bolsas de hojarasca con mallas de dos tamaños diferentes que contenían hojas de Laurus nobilis o palitos de abedul, distribuidas de manera aleatoria por 3 y 7 meses tanto sobre la superficie del suelo como a 10–15 cm de profundidad. La replicación dentro del sitio evaluó variabilidad especial en la pérdida de masa. En los BTM el tipo de hojarasca fue el factor biológico más importante que afectó la descomposición (hojas >madera), mientras que el tamaño de la malla y la profundidad tuvieron un rol menos importante. La comparación de BTB y BTM mostró que las variables climáticas ejercieron un papel preponderante en la descomposición. El modelo global Yasso07 proporcionó una explicación modesta de las tasas de descomposición. Las múltiples diferencias entre biomas sugieren que los BTM, con sus altas tasas de almacenamiento de carbono, deben ser considerados de manera explícita cuando se desarrollan teorías y modelos de ciclado de carbono en los trópicos.